PERANCANGAN MAIL CLIENT MENGGUNAKAN MEKANISME CREATE FOLDER OTOMATIS - Kusumaningrum, Anggraini; Ayuningtyas, Astika; Sipayung, Lely Delvia (Compiler, 2017)
The development of computer technology and telecommunications right now has changed the way society communicates. The technology used to communicate exists since the first Internet presence, that is to say by using the electronic mail. Email is a technology that allows everyone to communicate by sending messages or files. As with other ways that can be used to read and send emails, use the email client application. Email client is an application installed on a computer device used to access the email account on an email server, the email client does not need to use a browser application. But as long as this classification on email is still done manually on the part where the file storage download. To resolve the issue ranking of emails can be done automatically according to the name of the subject of e-mail, messages or files that are entered on the e-mail client of the application can then be downloaded and the data to download are stored in the folder that corresponds to the name of the subject e-mail, so that a message or file will be stored in a folder, it gives the convenience classification for mail client application mail user electronic with the number of messages or files that are much more consistent with the existing keywords in the subject of the email. This email client application can create folders automatically when downloading messages. Then, the downloaded file will be stored in the folder corresponding to the name of the subject. The file extension downloaded * .ml, the file can be opened via the mail client application. The mail client application can run on Windows and Linux operating systems.